2010
DOI: 10.1080/19361610.2011.529412
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Visual Situational Cues and Difficulty of Removal in Creating Deterrence: The Limitations of Electronic Article Surveillance Source Tagging in the Retail Environment

Abstract: Shrinkage continues to be a considerable cost to the retail industry, with a recent estimate suggesting that globally it could be as much as $278 billion a year. In addition, it is a problem that has proved difficult to resolve, despite billions of dollars of investment every year in new technologies by loss-prevention practitioners. A relatively common approach to try to reduce the extent of the problem has been the application of electronic article surveillance tags to retail products, either in the form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…The 1990s produced tags which could be sewn into or heat-sealed onto items of clothing at the point of manufacture (DiLonardo 2015). This process of source-tagging has become increasingly popular over the past decade, particularly among retailers since it ensures better consistency in tag application and it removes the requirement of retailers to train and resource staff to tag items in store (Beck and Palmer 2010). More recently, retailers have experimented with the use of RFID EAS tags albeit primarily as a way of monitoring stock levels as opposed to controlling theft (see Jones et al 2005).…”
Section: On the Design And Development Of Security Tagsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 1990s produced tags which could be sewn into or heat-sealed onto items of clothing at the point of manufacture (DiLonardo 2015). This process of source-tagging has become increasingly popular over the past decade, particularly among retailers since it ensures better consistency in tag application and it removes the requirement of retailers to train and resource staff to tag items in store (Beck and Palmer 2010). More recently, retailers have experimented with the use of RFID EAS tags albeit primarily as a way of monitoring stock levels as opposed to controlling theft (see Jones et al 2005).…”
Section: On the Design And Development Of Security Tagsmentioning
confidence: 99%
“…This ranged from making comparisons between (1) similar but untagged products in the same store (Retailer B 2015), (2) different stores in which the specific tags under evaluation were not installed (Farrington et al 1993;Bamfield 1994;Hayes and Blackwood 2006;Beck and Palmer 2010;Downs et al 2011), and (3) the store chain average more generally (DiLonardo and Clarke 1996). The trial reported in Retailer A (2015) did use a comparison group but only in relation to changes in sales and availability.…”
Section: Effectmentioning
confidence: 99%
See 3 more Smart Citations